Demand generation and social mobilisation for integrated community case management (iCCM) and child health: Lessons learned from successful programmes in Niger and Mozambique - Alyssa B Sharkey; Sandrine Martin; Teresa Cerveau; Erica Wetzler; Rocio Berzal (Edinburgh University Global Health Society, 2014)
We present the approaches used in and outcomes resulting from integrated community case management (iCCM) programmes in Niger and Mozambique with a strong focus on demand generation and social mobilisation. We use a case study approach to describe the programme and contextual elements of the Niger and Mozambique programmes. Awareness and utilisation of iCCM services and key family practices increased following the implementation of the Niger and Mozambique iCCM and child survival programmes, as did care-seeking within 24 hours and care-seeking from appropriate, trained providers in Mozambique. These approaches incorporated interpersonal communication activities and community empowerment/participation for collective change, partnerships and networks among key stakeholder groups within communities, media campaigns and advocacy efforts with local and national leaders. iCCM programmes that train and equip community health workers and successfully engage and empower community members to adopt new behaviours, have appropriate expectations and to trust community health workers' ability to assess and treat illnesses can lead to improved care-seeking and utilisation, and community ownership for iCCM.